2011
DOI: 10.1080/17429145.2010.516407
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of binary combinations of manganese with other heavy metals on metal uptake and antioxidative enzymes inBrassica junceaL. seedlings

Abstract: The present study investigates the interactive mechanism involved during the uptake of heavy metals and stress tolerance in Brassica juncea L. seedlings under the influence of Mn(II) in binary combinations with Cr(VI), Ni(II), Co(II) and Cu(II) in terms of changes in antioxidative enzymes-superoxide dismutase (SOD), guaiacol peroxidase (GPX), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR). The order of uptake of heavy metals by the seedlings in single metal solutions was observed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
5
0
1
Order By: Relevance
“…Between the two metals, removal rates for Mn were higher than that for Cr. High Mn uptake was also observed in previous studies with other plants (Kaur et al, 2011; Kropfelova et al, 2009; Marchand et al, 2010). While comparing the efficiencies of microcosms and mesocosms in metal removal, we found that mean Cr removal was clearly higher in mesocosm than in microcosm (90.4% and 82.8%, respectively), while this difference was less pronounced in the case of Mn removal (94.5% in mesocosm and 91.8% in microcosm).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Between the two metals, removal rates for Mn were higher than that for Cr. High Mn uptake was also observed in previous studies with other plants (Kaur et al, 2011; Kropfelova et al, 2009; Marchand et al, 2010). While comparing the efficiencies of microcosms and mesocosms in metal removal, we found that mean Cr removal was clearly higher in mesocosm than in microcosm (90.4% and 82.8%, respectively), while this difference was less pronounced in the case of Mn removal (94.5% in mesocosm and 91.8% in microcosm).…”
Section: Discussionsupporting
confidence: 85%
“…Second, it was observed that if added at higher concentrations of 2–5 mg L −1 to Cr‐containing solutions, Mn significantly reduced Cr uptake and ameliorated the adverse effects of Cr on chlorophyll content and biomass in H. verticillata (Sinha et al, 1993). Further, Kaur et al (2011) found that in binary combinations of Mn and Cr, uptake of both the metals was inhibited in Brassica juncea . Therefore, we wanted to find out whether in spite of these antagonistic interactions between the two metals, I. aquatica could effectively remove Cr and Mn from aqueous medium containing their binary mixture.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive amount of metal in the soil may facilitate other metals to be taken up by plants and also may hinder absorbance; hence, no specified reason can be drawn. , Zn is a structural component of several enzymes and thus affects the metabolism, pollen structure, and yield. , Therefore, the influence on pod development, seed number, and weight was observed. , Similarly, Cu at less than threshold level stimulates plant growth and also influences the uptake of other nutrients and metal ions from the soil. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Besides the differential effects that heavy metal toxicity has in the uptake of essential elements as described above, the interaction between these elements further complicates the issue. Some studies have also reported that the addition of an essential element can reduce the toxic effect of other heavy metals [ 91 ]. Podar et al [ 34 ] reported that extra Zn could supress Cd uptake in B. juncea plants growing in Cd-contaminated soil, compared to the control with regular amounts of the essential element.…”
Section: Micronutrient Statusmentioning
confidence: 99%